CORPORATE CULTURE AS A FIELD OF SOCIAL SPACE - Shatalova, Y. O. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
This article seeks to address a corporate culture as a field of social space. Based on the ideas of P. Bourdieu, the corporate culture is represented by the field of social space. This field of social space has a complex character and it serves as the unity of certain principles, values, rules of conduct, activities, games of the members of a corporation. And as a consequence, the field of social space is part of the strategy to achieve the success of the corporation in the market. As well as the field of social space, the corporate culture has its own structure, rules, specific patterns and logic of functioning. The corporate culture is a specific system of relations of various subcultures in the corporation, determined structurally and functionally.